Beyond racial capitalism co-operatives in the African diaspora - Hossein, Caroline Shenaz 1971- (Oxford University Press, 2023)
"Knowledge-making in the field of alternative economies has limited the inclusion of Black and racialized people's experience. In Beyond Racial Capitalism the goal is close that gap in development through a detailed analysis of cases in about a dozen countries where Black people live and turn to co-operatives to manage systemic exclusion. Most cases focus on how people use group methodology for social finance. However, financing is not the sole objective formany of the Black people who engage in collective business forms; it is about the collective and the making of a Black social economy. Systemic racism and anti-Black exclusion create an environment where pooling resources, in kind and money, becomes a way to cope and to resist an oppressive system. This book examines co-operatives in the context of racial capitalism-a concept of political scientist Cedric J. Robinson's that has meaning for the African diaspora who must navigate, often secretly and in groups, the landmines in business and society. Understanding business exclusion in the various cases enables appreciation of thecivic contributions carried out by excluded racial minorities. These social innovations by Black people living outside of Africa who build co-operative economies go largely unnoticed. If they are noted, they are demoted to an "informal" activity and rationalized as having limited potential to bringabout social change. The sheer determination of Black diaspora people to organize and build co-operatives that are explicitly anti-racist and rooted in mutual aid and the collective is an important lesson in making business ethical and inclusive."